Analog Circuit Applications Based on All‐2D Ambipolar ReSe2 Field‐Effect Transistors. (2nd April 2019) - Lee, Ko‐Chun; Yang, Shih‐Hsien; Sung, Yung‐Shang; Chang, Yuan‐Ming; Lin, Che‐Yi; Yang, Feng‐Shou; Li, Mengjiao; Watanabe, Kenji; Taniguchi, Takashi; Ho, Ching‐Hwa; Lien, Chen‐Hsin; Lin, Yen‐Fu
Abstract: Complementary circuits based on 2D materials show great promise for next‐generation electronics. An ambipolar all‐2D ReSe2 field‐effect transistor (FET) with a hexagonal boron nitride gate dielectric is fabricated and its electronic characteristics are comprehensively studied by temperature dependence and noise measurements. Ambipolar transfer characteristics are achieved owing to the tunable Fermi level of the graphene contact and negligible and 30 meV Schottky barrier heights for the n‐ and p‐channel regimes, respectively. An inverter is also fabricated to demonstrate ambipolar ReSe2 FET operation in a logic circuit. Furthermore, a p/n switchable unipolar FET is designed and shows potential for building complimentary circuits from a signal device. This work demonstrates the potential of all‐2D ReSe2 FETs and makes available new approaches for designing next‐generation devices. Abstract : An all‐2D ReSe2 field‐effect transistor (FET) with graphene contact, which enables switching between n‐ and p‐type behaviors, is fabricated. The transport mechanism is comprehensively studied through both temperature dependence and noise measurements. A "single‐device" ambipolar ReSe2 FET is further applied to build an inverter function. This work demonstrates the promise of all‐2D materials‐based ambipolar FET for analog circuit applications.